Penerapan Prosedur Audit atas Akun Piutang Usaha: Studi pada Kantor Akuntan Publik Bayudi, Yohana, Suzy, Arie (KAP BYSA) Cabang Semarang - Muhammad Fathur Rohim; Muhammad Agil Al Hadif (Journal of Economics, Management, and Accounting, 2025)
This study aims to analyze the implementation of audit procedures on accounts receivable at the Public Accounting Firm Bayudi, Yohana, Suzy, Arie (KAP BYSA), Semarang Branch. A descriptive case study approach was used with a qualitative method. Data were collected through internal audit documentation, non-participatory observation, and literature review of audit standards such as SA 315, SA 330, SA 500, and SA 530. The findings indicate that auditors generally comply with professional audit standards, particularly in gathering audit evidence (SA 500) and understanding the entity and its environment (SA 315). However, the application of SA 330 and SA 530 remains suboptimal, especially regarding risk response and the use of statistically-based sampling methods. Key findings include weaknesses in internal control documentation, non-conservative allowance estimation for doubtful accounts, and insufficient disclosure of related-party receivables. This study emphasizes the need to improve documentation quality, adopt audit technologies such as ACL, and enhance risk-based substantive testing strategies. Strengthening these aspects is expected to enhance the effectiveness of accounts receivable audits and contribute to the integrity of financial reporting, thereby safeguarding stakeholder interests.